2016
DOI: 10.1515/enr-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of boron and vitamin E on ethylene glycol-induced renal crystal calcium deposition in rat

Abstract: Efficient effect of boron and Vit E supplements, separately and in combination, has a complimentary effect in protection against the formation of kidney stones, probably by decreasing oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Ethylene glycol is commonly used to form nephrolithiasis model in rats to simulate the formation of kidney stones in humans [ 32 ]. Nephrolithiasis was evidenced by both microscopic urine analysis and kidney histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene glycol is commonly used to form nephrolithiasis model in rats to simulate the formation of kidney stones in humans [ 32 ]. Nephrolithiasis was evidenced by both microscopic urine analysis and kidney histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…12 Boron, is an element that decreases the cellular damage caused by oxidative stress (OS). 13 Free radicles (FRs) initiate cell reactive oxygen species (ROS) induced cell damage and cell death. 14 Cerium oxide (CeO2) also has an antibacterial activity 15 due to the redox potential of CeO2, the oxidation state of Ce changed from Ce 3+ and Ce 4+ depending on the external environment, this redox potential facilitates the inhibiting the bacterial growth and scavenging FRs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been suggested that boron inhibits apoptosis by stabilizing the mitochondrial membrane structure (Routray, Ali, 2019). In fact, the mechanisms of boric acid actions (source of boron) on various organs were well documented (Bahadoran et al, 2016;Khaliq et al, 2018). Despite these promising outcomes, additional investigations are strictly needed to elucidate possible mechanisms of the other boron compounds as therapeutic agents.…”
Section: Lithium Tetraborate Reduces the Heart Injury Induced By Rena...mentioning
confidence: 99%